Extreme value theory in engineering - Castillo, Enrique, 1946- (Statistical modeling and decision science., 1988)
This book is a comprehensive guide to extreme value theory in engineering. Written for the end user with intermediate and advanced statistical knowledge, it covers classical methods as well as recent advances. A collection of 150 examples illustrates the theoretical results and takes the reader from simple applications through complex cases of dependence.